MiR‐466 is putative negative regulator of Coxsackie virus and Adenovirus Receptor. Issue 2 (10th December 2014) - Lam, W.Y.; Cheung, Ariel C.Y.; Tung, Christine K.C.; Yeung, Apple C.M.; Ngai, Karry L.K.; Lui, Vivian W.Y.; Chan, Paul K.S.; Tsui, Stephen K.W.
Abstract : This study aimed at elucidating how Coxsackie B virus (CVB) perturbs the host's microRNA (miRNA) regulatory pathways that lead to antiviral events. The results of miRNA profiling in rat pancreatic cells infection models revealed that rat rno‐miR‐466d was up‐regulated in CVB infection. Furthermore, in silico studies showed that Coxsackie virus and Adenovirus Receptor (CAR), a cellular receptor, was one of the rno‐miR‐466d targets involved in viral entry. Subsequent experiments also proved that both the rno‐miR‐466d and the human hsa‐miR‐466, which are orthologs of the miR‐467 gene family, could effectively down‐regulate the levels of rat and human CAR protein expression, respectively. Abstract : The Rat miR‐466d expression was up‐regulated during CVB virus infection. Human and rat miR‐466 species showed target 'seed' regions on CAR mRNA 3′‐UTRs. miR‐466 species down‐regulated CAR protein expression in rat and human, respectively. miR‐466 species were putative negative regulator of CAR. We reported that miR‐466 species had correlation to the anti‐viral effect on CVB infection.